Концептуальные и организационно-методические основы создания "Украинского социологического архива и банка данных социальных исследований" - Головаха, Е. (Социология: теория, методы, маркетинг, 2000)
In the world, sociological information archives have existed for over fifty years. Positive and negative experience of sociological archives organization and functioning should be regarded for better conceptual and organizational methods development of Ukrainian Sociological Archive and Data Bank on Social Research freely accessible for all interested persons and organizations that need retrospective and current information on public opinion development in Ukraine, on social, political and economic orientations of population. We analyzed the foreign experience related to sociological archives and decided to concentrate our attention on structure optimization, description completeness and search simplicity. According to the offered conception, the data massives are classified as belonging to the three main storage and search categories: 1) sociological researches conducted with respect to all professional methodological requirements; 2) mass opinion polls conducted by professional public opinion service companiesmeeting the necessary organizational and methodical requirements; 3) polls and researches that cannot be regarded as absolutely reliable and meeting all the necessary (for obtaining quality information) requirements.